A novel DNA damage repair-related signature for predicting prognositc and treatment response in non-small lung cancer - Li, Ling; Zou, Bao-jia; Zhao, Juan-zhi; Liang, Jia-bi; She, Zi-yue; Zhou, Wen-ying; Lin, Si-xiao; Tian, Lin; Luo, Wen-ji; He, Fa-zhong (Frontiers in Oncology, 2022)
DNA damage repair (DDR) is essential for maintaining genome integrity and modulating cancer risk, progression, and therapeutic response. DDR defects are common among non-small lung cancer (NSCLC), resulting in new challenge and promise for NSCLC treatment. Thus, a thorough understanding of the molecular characteristics of DDR in NSCLC is needed. Here, we systematically analyzed DDR alterations in NSCLC by integrating multiple publicly available datasets. NSCLC patients were classified into C1 subtype and C2 subtype based on prognostic DDR-related genes, with different clinical outcomes and unique molecular characteristics. The C1 subtype was characterized with worse prognosis, higher proportion and numbers of DDR mutations, unique immune profile with down-regulation of immune checkpoints, and less responsive to immune therapy. Patients in C2 subtype, which had distinct clinical, molecular, mutation and immune characteristics, tend to have superior survival and responsive to immunotherapy. Finally, we successfully established and validated a prognostic six DDR-related gene model according to CDC25C, NEIL3, H2AFX, NBN, XRCC5, and RAD1 expression, and made it possible for NSCLC patient stratification and personalized cancer management. Overall, this molecular classification based on DDR pathway profiling contributes to personalized clinical management and provides potentially therapeutic targets for NSCLC.